Lead‐Free Double Perovskite Cs2AgInCl6 - Liu, Ying; Nag, Angshuman; Manna, Liberato; Xia, Zhiguo (Angewandte Chemie International Edition, 2021)
Lead‐free halide perovskites have drawn wide attention as alternatives to their toxic and poorly stable lead‐based counterparts. Among them, double perovskites with Cs2AgInCl6 composition, often doped with various elements, have been in the spotlight owing to their intriguing optical properties, namely, self‐trapped exciton (STEs) emission and dopant‐induced photoluminescence. This interest has sparked different synthesis approaches towards both crystals and nanocrystals, and the exploration of many alloy compositions with mono‐ and trivalent cations other than Ag+ and In3+. In this Minireview we describe the recent developments on Cs2AgInCl6 bulk crystals and nanocrystals, their synthesis strategies, intrinsic optical properties, and tunable photoluminescence originating from different alloying and doping effects. We also discuss progress on computational studies aimed at understanding the thermodynamic stability, the role of defects, and the origin of photoluminescence in relation to the STEs and the direct band gap character. Lead‐free halide perovskites such as the easily synthesized double perovskite Cs2AgInCl6 have generated great attention as promising alternatives to lead‐based counterparts. This Minireview takes a close look at Cs2AgInCl6 materials in the form of bulk crystals as well as nanocrystals in terms of doping engineering, photoluminescence modification, and fundamental theoretical understanding.